Spiritual Marketing in Light of Paternal Leadership: An Applied Study in the General Company for Food Products - Alkhazraje, Mohammed Edan (Universitas Airlangga, 2025)
Background: Presenting literary contributions to parental leadership and spiritual marketing and focusing on the advantages and benefits that can be benefited from on the practical side Objective: This research aims to study and analyze the relationship between paternal leadership and spiritual marketing. The problem of the research was expressed in questions: Was the General Company for Food Products able to employ paternal leadership in achieving spiritual marketing? What is the nature of the relationship between paternal leadership and spiritual marketing? Method: The General Company for Food Products was chosen as a research community, and a random sample of directors and officials in the company was chosen as a sample for the research. A five-point questionnaire was used to collect data. The number of respondents reached (48). To analyze the data, the descriptive analytical approach was adopted using SmartPLS Results: There is an impact relationship and connection between paternal leadership and spiritual marketing, as the paternal leadership approach contributes greatly to localizing the main relationship with subordinates, encourages them to work, and motivates them to make efforts, and this is consistent with the philosophy of spiritual marketing Conclusion: Directing the efforts of the company’s senior leadership to define and promote a clear spiritual vision for the company that focuses on morals, values, and lofty principles and relying on the paternal leadership approach in achieving them by encouraging subordinates to carry out business and marketing activities in accordance with standards, ethics, and integrity to achieve the goals of spiritual marketing Keywords: paternal leadership; spiritual marketing; autocratic leadership; ethical leadership; good leadership